The modeling framework of the coupled human and natural systems in the Yellow River Basin - Shan Sang; Yan Li; Shuang Zong; Lu Yu; Shuai Wang; Yanxu Liu; Xutong Wu; Shuang Song; Xuhui Wang; Bojie Fu (Geography and Sustainability)
A mechanistic understanding and modeling of the coupled human and natural systems (CHANS) are frontier of geographical sciences and essential for promoting regional sustainability. Modeling regional CHANS in the Yellow River Basin (YRB) featuring high water stress, intense human interference, and a fragile ecosystem has always been a complex challenge. Here, we propose a conceptual modeling framework to capture key human-natural components and their interactions, focusing on human-water dynamics. The modeling framework encompasses five human (Population, Economy, Energy, Food, and Water Demand) and five natural sectors (Water Supply, Sediment, Land, Carbon, and Climate) that can be either fully interactive or standalone. The modeling framework, implemented using the system dynamics (SD) approach, can well reproduce the basin's historical evolution in human-natural processes and predict future dynamics under various scenarios. The flexibility, adaptability, and potential for integration with diverse methods position the framework as an instructive tool for guiding regional CHANS modeling. Our insights highlight pathways to advance regional CHANS modeling and its application to address regional sustainability challenges.